Improving students engagement through social media: A case study of a private university in Malaysia using Facebook - Sim, Tze Ying *; Dewika, M *; Devandran, A. * (International Academy Publishing (IAP), 2014)
This research looks into implementation of Facebook in six different courses covering Science, Engineering and Technology subjects. The initial purpose of using Facebook in the class is to communicate with the students more effectively, as communication through the formal channel (through learn management system) had not been successful. It is expected that by sending two to three notices per week to the students as a gentle reminder for reading material, assignments or even tests, students would be more motivated to engage in the course content. The research results showed that students are positive in using Facebook as an engagement tool. The engagement also encourages their participation in class, and enhances their interest towards the subject content. Features that influenced this engagement are also looked into.